The Harvard-MIT-NEMC Research Training Program in Medical Informatics - Greenes, Robert A.; Octo Barnett, G.; Pauker, Stephen G.; Szolovits, Peter; Weinstein, Milton C. (Yearbook of Medical Informatics, 1994)
The Harvard-MIT-NEMC Research Training Program in Medical Informatics brings together five separate research groups to provide a diversified training experience in Boston with sponsorship by the National Library of Medicine. This program offers predoctoral and postdoctoral programs, supplemented by many opportunities for collegial exchange and interaction among the groups.
Keywords: Medical Informatics; Tranining Programs